Effect of ocular reconstruction on brain function and structure in people with age-related cataracts: a prospective controlled clinical trial. (October 2016) - Lin, Haotian; Zhang, Li; Chan, Kevin; Qiu, Yingwei; Lin, Duoru; Chen, Wan; Chen, Hui; Liu, Yizhi; Chen, Weirong
Abstract: Background: Healthy ageing is accompanied by simultaneous decline of visual and neural function. Studies in animals and humans provide converging evidence that these functions' decrease is mostly associated with structural change in ocular and brain structure. We investigated whether regaining visual function after ocular reconstruction was associated with functional and structural changes in the brain. Methods: We did a prospective controlled clinical trial including 21 consecutive typical ageing patients (42 eyes; mean age 63·14 years, SD 7·82) with decreased visual function and diagnosis of bilateral age-related cataracts requiring phacoemulsification surgery and multifocal or monofocal intraocular lens implantation. Before surgery and 1 week, 3 months, and 6 months after surgery, we measured visual function parameters including best corrected visual acuity (BCVA), contrast sensitivity, straylight values, and pattern visual evoked potential, and we evaluated brain function and structure with the Mini-Mental State Examination and functional magnetic resonance imaging. Paired-t test, ANOVA, and post-hoc tests were used to compare preoperative and postoperative results. The study was approved by the ethics committee of Zhongshan Ophthalmic Center of Sun Yat-sen University. Written informed consent was obtained. This trial is registered withClinicalTrials.gov, NCT02644720 . Findings: These 21 patients with age-related cataracts had visual and brain function decline and structural alterations before surgery compared with 21 age-matched and sex-matched healthy controls without cataracts. BCVA (assessed by LogMAR) 1 week after operation (mean −0·02, SD 0·01) was significantly improved compared with baseline (mean 0·61, SD 0·06; difference 0·633, 95% CI 0·51 to 0·76, p<0·0001). Significant functional improvements measured by fractional amplitude of low frequency fluctuation values were shown in the visual cortex at 3 months after ocular reconstruction (mean 0·12, SD 0·06), compared with values before surgery (mean 0·05, SD 0·06; difference −0·076, 95% CI −0·10 to 0·05, p=0·004). A significant increase in grey matter volume (voxel-based morphometry value) occurred in the vision-related area 3 months after surgery (mean 0·42, SD 0·07) compared with baseline (mean 0·37, SD 0·09; difference −0·06, 95% CI −0·08 to −0·03, p<0·0001). No significant change was noted in non-visual cortical regions 3 months postoperatively. Interpretation: These results suggest that ocular reconstruction to restore vision is associated with improvements in brain function and structure, even after initial of cerebral function degeneration, which might have been caused by visual decline and blindness in our study group. Funding: This work was supported by theNatural Science Foundation of Guangzhou City (81570889, 81270980 ), theScience and Technology Program of Guangdong Province, China (2013B021800054, 2013B020400003, 15570001 ), and the Clinical Research and Translational Medical Center Program in Guangzhou City.